GE_GERICHTE P/17013/2025 vom 1. Oktober 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;CONTRAINTE(DROIT PÉNAL);ACTE DE POURSUITE(PROCÉDURE LP);SUBROGATION;OBLIGATION D'ENTRETIEN | CPP.310; CP.181; CC.289.al2